K2-99: a subgiant hosting a transiting warm Jupiter in an eccentric orbit and a long-period companion - Smith, Alexis M. S.; Wolthoff, Vera (Arxiv, 2016)
We report the discovery from K2 of a transiting planet in an 18.25-d, eccentric (0.19$±$ 0.04) orbit around K2-99, an 11th magnitude subgiant in Virgo. We confirm the planetary nature of the companion with radial velocities, and determine that the star is a metal-rich ([Fe/H] = 0.20$±$0.05) subgiant, with mass $1.60^{+0.14}_{-0.10}~M_\odot$ and radius $3.1± 0.1~R_\odot$. The planet has a mass of $0.97±0.09~M_{\rm Jup}$ and a radius $1.29±0.05~R_{\rm Jup}$. A measured systemic radial acceleration of $-2.12±0.04~{\rm m s^{-1} d^{-1}}$ offers compelling evidence for the existence of a third body in the system, perhaps a brown dwarf orbiting with a period of several hundred days.